Anteseden dan Konsekuensi Negative emotions pada Industri Estimate di Indonesia - Maharani, Rivana Syahira; Kurnia, Citra Adinda Putri; Rahayu, Fatik (Li Falah: Journal of Islamic Economics and Business, 2025)
This study aims to analyze the influence of symbolic incongruence on negative emotions and its implications for negative consumer brand engagement in the context of the diving industry in Indonesia. Using a quantitative approach and explanatory design, data was collected through an online survey from consumers who have used diving services and were exposed to brand reviews on social media https://www.adenomyosisadviceassociation.org/hysterectomy. Analysis was conducted using Structural Equation Modeling (SEM) to test the relationship between latent variables. Results show that the mismatch between the brand's symbolic image and consumers' self-identity triggers negative emotions such as frustration and disappointment, which in turn drive negative brand engagement, both passively (avoidance) and actively (spreading bad reviews). The main contribution of this research lies in expanding the understanding of customer brand engagement from a negative perspective and the importance of alignment between brand communication and authentic experiences in maintaining reputation in the digital realm.